Autopoiesis and evolution: the role of organisms in natural drift. (October 2021) - Raimondi, Vincenzo
Genetic reductionism is increasingly seen as a severely limited approach to understanding living systems. The Neo-Darwinian explanatory framework tends to overlook the role of the organism for an understanding of development and evolution. In the current fast-changing theoretical landscape, the autopoietic approach provides conceptual distinctions and tools that may contribute to building an alternative framework. In this article, I examine the implications of the theories of autopoiesis and natural drift for an organism-centered view of evolution. By shifting the attention from genes to ontogenetic organism-niche configurations and their transformations over generations, this approach presents a compelling perspective on the role of organismal behavior in guiding phylogenetic drift.